Shaping the Future Together: The Inaugural Vision for AI and Tech in Behavioral and Social Sciences - Taheri, Morteza (AI and Tech in Behavioral and Social Sciences, 2023)
In the realm of contemporary research, the fusion of artificial intelligence (AI) and social sciences stands as a beacon of interdisciplinary innovation, driving forward our understanding of technology’s multifaceted impact on society. This integration, is not just a parallel growth of two fields but a necessary convergence that illuminates the societal ramifications of AI advancements. The exploration of AI’s expected impacts through social science inquiries is pivotal, offering a lens to view AI’s societal roles with greater clarity and depth. As we launch the inaugural issue of "AI and Tech in Behavioral and Social Sciences," our commitment is to forge a path for groundbreaking research that spans these diverse yet interconnected domains. Through this journal, we aspire to cultivate a rich discourse that not only advances scientific knowledge but also contributes to the ethical, inclusive, and socially responsible development of AI technologies. Our journey begins with a deep belief in the power of interdisciplinary research to illuminate the complexities of human behavior and societal transformation in the age of AI.